Using Individual Values Of Information Technology Professionals To Improve Software Development Management Practices In Thailand - Jirachiefpattana, Waraporn (Asian Academy of Management (AAM), 2015)
Management of software development is a vital factor which can lead to the success of software projects. The most important component involved in the project is the composition of the team members. Several cross cultural and psychological research studies indicate that human values influence human behaviour. Therefore, the individual values of Thai Information Technology (IT) professionals who include the project manager, the systems/business analyst and the programmer also impact the software development management practices. This research reveals that Thai IT workers' selfdirection influences all practice areas of software development. In addition, and apart from this individualist value, others such as the benevolence, universalism, conformity and achievement of these professionals are also significant values.